The effect of Ashtanga-Vinyasa Yoga method on air force pilots’ operational performance - Santos, Sara; Melo, Filipe; Fernandes, Orlando; Parraca, José Alberto (Frontiers in Public Health, 2024)
Introduction: In today's military landscape, optimizing performance and bolstering physical health and mental resilience are critical objectives. Introducing a 12-week Ashtanga Vinyasa Yoga Supta Method (AVYSM) to the training protocol of military trained Airforce pilots, we aim to assesses the feasibility and impact of the method. Materials and Equipment: Borg Scale assesses the intensity level of physical activity during the intervention. Flight simulator data gauges operational performance responses. Postural control responses are measured using a force platform, stress responses are monitored via heart monitor, and handgrip dynamometry will measure strength. Respiratory capacity is assessed using a spirometer, body composition is evaluated using impedance balance, and aviation-related questionnaires are administered before and after the intervention period. Methods: In a randomized controlled trial, the totality of pilots from the "Masters in Military Aeronautics: aviator pilot specialist" course at the Portuguese Air Force Academy (PAA) were randomly assigned to the yoga intervention or the waiting list control groups, with participants providing written informed consent. The control group followed protocolized course classes for 12 weeks, while the intervention group integrated two weekly one-hour yoga sessions into their course. (Anticipated) Results: The PAA has approved the implementation of this intervention protocol at Airbase 11 in Beja, highlighting its significance for the organization's policy makers. We hypothesize that this method will enhance operational performance and, subsequently, elevate flight safety. Discussion: This research's potential extends beyond the PAA, as it can be adapted for use in Airforce departments of other nations and various military contexts.